Contested minorities in the 'New Europe': national identities in interwar Eastern and Southeastern Europe. Issue 4 (8th August 2021) - Palko, Olena; Foster, Samuel
ABSTRACT: Among the many challenges facing the new, or enlarged, nation-states that arose on the territories of the former empires of Central, Eastern and South-Eastern Europe in 1918, few were as vexing or complex as the so-called 'minorities question'. Thousands of disparate communities suddenly discovered that they now existed as minorities, often in areas adjacent to their designated homelands. As an introduction to this special issues, this article provides an overview of the key concepts and historical debates surrounding the interwar regional minorities question. It also seeks to challenge underlying assumptions that characterise such communities as perpetual victims of nationalist animosity.